The Military Vocabulary as a Component of Achilles Tatius’s Idiostyle - Chakal, Inesa (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The article attempts to characterize military vocabulary as an integral component of Achilles Tatius’s idiostyle, of an ancient Greek writer of the 2nd century AD, the author of one of the first love novels that have survived to our days in full – "Leucippe and Clitophon".The purpose of the research was the classification, systematization and analysis of features of the vocabulary of the military sphere detected in the text of the novel, which required the use of analytical-descriptive, structural, quantitative methods. In the structure of the lexical idiosystem of Achilles Tatius’s novel the military vocabulary occupies a special place and includes 134 lexemes (706 word usages).The scientific novelty of the obtained results lies in the fact that, for the first time, a systematic analysis of the vocabulary of military affairs in the work "Leucippe and Clitophon" was carried out in the article; military lexemes-terms were classified according to the lexical-semantic criterion into 10 thematic groups, among which the largest were "Military actions, maneuvering, tactics and strategy", "Military weapons and their use", and "Armed conflict"; the dominant ones among the military vocabulary (ὁ λῃστής, ἡ ναῦς, ὁ στρατηγός, τὸ ξίφος, ὁ πόλεμος, τὸ βέλος, ὁ σίδηρος, ὁ βουκόλος, ὁ στρατιώτης) are differentiated, which are considered as key words; the stylistic and functional role of individual lexical units belonging to the analyzed thematic groups is traced.Among the lexemes of different thematic groups, non-equivalent vocabulary was found (τὸ ζῶμα, ὁ λοχαγός, ὁ λόχος, ὁ ὁπλίτης, ὁ παραστάτης, ὁ πελταστής, ὁ στρατηγός, ὁ βουκόλος, ἡ φάλαγξ), which serves to express military concepts absent in another culture or language, and a series of co-rooted words (the largest – 12 lexical units), which have different lexical meanings and belong to different parts of speech (ὁ στρατηγός, ὁ στρατιώτης, στρατικός, ὁ συστράτηγος, ἡ στρατεία, τό στράτευμα, ἡ στρατιά, τὸ στρατεπον, ὁ στρατος, συστρατεύομαι, στρατοπεδεύομαι, στρατεύομαι). The names of military concepts, objects, phenomena are included in the structure of many artistic figures (epithets, similes, oxymorons, hyperboles, metaphors, paraphrases).Conclusions. Military terms and lexemes, skillfully used by Achilles Tatius, fully fulfill their definite-nominative function and influence the figurative system of the work, thus creating the unique writer’s idiostyle.